Sex, Loyalty, and Betrayal : Migration and the Limits of Patriarchal Privilege - Deborah Cohen (IdeAs)
This article explores the consequences of Mexican migrants’ extramarital affairs on social relations within a community of undocumented migrants in Chicago, and the ways men attempt to limit their impact. My fieldsite for this exploration is The Eatery, a small Chicago restaurant in which migrants or their natal or extended family members worked and to which all were anchored. What I found was that men’s trysts were not merely tolerated; they were understood to not count. I argue that this arrangement upheld both the affairs and the patriarchal privilege that allowed them in the first place, even as it mitigated their probable negative effects on inter-migrants social relations. Thus, it fostered an individual’s ability to have extramarital relationships and became the vehicle for containing their destabilizing effects on the entire migrant community. Only in recognizing this containment can we begin to understand the larger social and cultural dislocations and array of losses that ground unauthorized migration.